Exemption from punishment and serving sentences: problems of systematization and improvement of legislation - Письменський, Є.О. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2015)
The article examines certain terminological and substantive shortcomings of the current criminal legislation of Ukraine in terms of regulating the institution of exemption from punishment and its enforcement. Keywords: exemption from punishment, exemption from serving part of the sentence, replacement of punishment with a more lenient one, forms of criminal liability

У статті розглядаються окремі термінологічні та змістовні вади чинного кримінального законодавства України в частині регламентації інституту звільнення від покарання та його відбування. Ключові слова: звільнення від покарання, звільнення від відбування частини покарання, заміна покарання більш м’яким, форми реалізації кримінальної відповідальності
Звільнення від покарання та його відбування: проблеми систематизації та вдосконалення законодавства